Free to choose ([S.l.] : Free to Choose Enterprise, 1980)
Five documentaries, each followed by a discussion, explore the history of the U.S. government's economic controls. The Great Depression of 1929, the failure of the Federal Reserve System, the welfare state, the need for competition and free trade, and the concept of freedom are some of the topics discussed.
v. 1.(1-2) The power of the market/ the tyranny of control -- v. 2.(3-4) Anatomy of crisis/from cradle to grave -- v. 3.(5-6) Created equal/what's wrong with our schools -- v. 4.(7-8) Who protects the consumer/who protects te worker -- v. 5.(9-10) How to cure inflation/how to stay free.
Keywords: DVD-ROMs.; Equality -- DVD-ROMs.; Capitalism -- DVD-ROMs.; Welfare state -- DVD-ROMs.